Teaching as a calling and well-being of Slovenian and Croatian teachers - Gradišek, Polona (Array, 2020)
In a sample of 347 elementary school subject teachers from Slovenia (N = 176) and Croatia (N = 171), the authors investigated teachers’ orientations to work (as a job, a career, and a calling) and their well-being with respect to different stages of teachers’ professional development. Results have shown the presence of a calling orientation to work and its positive relationship to job satisfaction and life satisfaction. Although significant differences between Slovenian and Croatian teachers were not expected due to shared historical, cultural and political background, some interesting differences were observed. The results of MANOVA showed that teachers differed significantly in their work orientations regarding nationality and the length of their working experience. Results were discussed in the context of stages of professional development and the social status of teachers in both countries.